Impact of multiple drug-resistant Gram-negative bacterial bacteraemia on infected pancreatic necrosis patients - Wu, Di; Jia, Yan; Cai, Wenhao; Huang, Yilin; Kattakayam, Arjun; Latawiec, Diane; Sutton, Robert; Peng, Jie (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction: Multiple drug-resistant Gram-negative bacterial (MDR-GNB) bacteraemia poses a serious threat to patients in hospital. Infected pancreatic necrosis (IPN) patients are a vulnerable population for infectious complications during hospitalization. This study aims to evaluate the impact of MDR Gram-negative bacteraemia on IPN patients. Methods: A case-control study was performed with data collected from January 1st, 2016 to July 1st, 2022 in a Chinese tertiary teaching hospital. Clinical data of the IPN patients with MDR-GNB bacteraemia were analysed and compared to a matched control group without MDR-GNB bacteraemia (case-control ratio of 1:2). Comparisons were preformed between with/without MDR-GNB bacteraemia and different severities of acute pancreatitis (AP), respectively. Independent predictors of overall mortality were identified via univariate and multivariate binary logistic regression analyses. Results: MDR-GNB bacteraemia was related to a higher mortality rate (62.5% vs. 8.3%, P < 0.001). Severe AP combined with MDR-GNB bacteraemia further increased mortality up to 81.3% (P = 0.025). MDR-GNB bacteraemia (Odds ratio (OR) = 8.976, 95% confidence interval (CI) = 1.805 - 44.620, P = 0.007) and severe AP (OR = 9.414, 95%CI = 1.742 - 50.873, P = 0.009) were independent predictors of overall mortality. MDR- Klebsiella pneumoniae were the most common causative pathogens. Conclusion: Higher mortality rate in IPN patients was related to MDR-GNB bacteraemia and further increased in severe AP patients combined with MDR-GNB bacteraemia.